Prospective study of predictive factors of changes in pain and hip function after hip fracture among the elderly. Issue 2 (February 2016) - Orive, M.; Anton-Ladislao, A.; García-Gutiérrez, S.; Las Hayas, C.; González, N.; Zabala, J.; Quintana, J.
Abstract Summary Our study identified pre-fracture variables, such as home status or function, that are directly or indirectly associated with frailty status before fracture. The prevention in the deterioration of those variables would improve the prognosis of those hip fractured, being this an important issue for the societies with increasingly aging population. Introduction This study was designed to identify predictors of pain and declines in function among elderly patients following a fall-related hip fracture. Methods Patients aged 65 or older with a fall-related hip fracture retrospectively completed pre-fracture status questionnaires (T0;n  = 740) and were then prospectively followed for 6 months (T1;n  = 546). Of these, 474 were randomly selected to complete an additional 18 months of follow-up (T2;n  = 356). Primary outcome measures were changes in the pain and function dimensions of the Western Ontario and McMaster Universities Osteoarthritis Index questionnaire's short form (WOMAC-SF). Potential predictors included sociodemographic variables, in-hospital and clinical pre- and post-fracture data, and activities of daily living at baseline and follow-up. Multivariate logistic regression was used for analysis. Results Predictors of worsening pain at T1 and/or T2 included living in a home care situation or nursing home before the fracture (OR at T1, 1.515; OR at T2, 2.749), and low pre-fracture pain (OR at T1, 1.028; OR at T2, 1.027). Predictors of deterioration in function at T1 and/or T2 included age ≥85 years (OR at T1, 2.714; OR at T2, 4.762), lower income (OR at T1, 1.755), high pre-fracture hip function (OR at T1, 1.029; OR at T2, 1.028), referral to rehabilitation upon discharge (OR at T1, 2.378; OR at T2, 2.881), and longer delay between fall and surgery (OR at T1, 1.133; OR at T2, 1.124). Conclusions Frailty before hip fracture is a predictor of greater post-fracture pain and deterioration in function. Given that exercise programs help prevent frailty, promoting exercise in elderly may improve the prognosis of hip fracture.